The political-economic scenario post-cold war and the neoliberal wave in Latin America: a case study of Brazil, Chile and Argentina. - Valenti, Luiza Pecis (2018)
This paper analyzes the impact of neoliberalism in Latin America in the late twentieth century taking account that there existed a strategy of hegemonic consolidation of the United States. Based on an exploratory and qualitative research, a contextualization about the international scenario during the period and the historical trajectory of neoliberalism in countries like Brazil, Argentina and Chile will be studied using concepts from the area of International Relations.